A strategy to enhance the photocatalytic efficiency of α-Fe2O3. (May 2021) - Keerthana, SP.; Yuvakkumar, R.; Ravi, G.; Kumar, P.; Elshikh, Mohamed Soliman; Alkhamis, Hussein H.; Alrefaei, Abdulwahed F.; Velauthapillai, Dhayalan
Abstract: The photocatalytic dye degradation of pure α-Fe2 O3 and different concentration of Co doped α-Fe2 O3 is explored. Facile hydrothermal method were employed to prepare pristine, 2% and 4% Co–Fe2 O3 nanoparticles. Further, synthesized product confirmation studies were employed from X-ray diffraction, UV–vis spectrometry, Fourier-transform infrared, Raman, scanning electron microscope and transmission electron microscope studies. The rhombohedral nanoparticles developed were enhanced photocatalytic action. Photocatalytic dye degradation studies were analyzed for prepared three samples and the photocatalytic efficacy of the obtained photocatalysts was compared experimentally. Methylene blue dye was degraded under UV-light irradiation with 364 nm. The results showed that 4% Co doped α-Fe2 O3 sample exhibited better dye degradation with 92% efficiency. The 4% doping of cobalt ions enhanced the photocatalytic property of Fe2 O3 and is a good candidate for methylene blue dye degradation above 90%. In addition, strategy for photocatalytic efficiency enhancement was proposed. Highlights: A strategy for photocatalytic efficiency enhancement was proposed. 4% Co–Fe2 O3 enhanced the photocatalytic activity. 4% Co–Fe2 O3 explored dye degradation with 92% efficiency. Cobalt ions doping enhanced Fe2 O3 photocatalytic property.